2012
DOI: 10.1128/iai.00236-12
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Notch and Wnt/β-Catenin Pathways in the Regulation of Hyperplasia and/or Colitis in Response to Bacterial Infection

Abstract: Notch and Wnt/␤-catenin signals play essential roles in intestinal development and homeostasis. Citrobacter rodentium induces transmissible murine colonic hyperplasia (TMCH) and various degrees of inflammation, depending upon the genetic background. We aimed at delineating the role of the Notch and Wnt/␤-catenin pathways in the regulation of colonic crypt hyperplasia and/or colitis following C. rodentium infection. During TMCH, relative levels of the Notch intracellular domain (NICD) increased significantly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 35 publications
4
55
0
Order By: Relevance
“…We and other investigators have also demonstrated that curcumin inhibits several important signaling pathways including Notch and Wnt signaling (4,132). Interestingly, it was found that curcumin could inhibit mammosphere formation and could also decrease the amount of aldehyde dehydrogenase-positive cells in normal and malignant breast cancer cells through the inhibition of Wnt signaling (23), suggesting the inhibitory effects of curcumin on breast cancer stem cells (23).…”
Section: Natural Products and Human Healthmentioning
confidence: 93%
“…We and other investigators have also demonstrated that curcumin inhibits several important signaling pathways including Notch and Wnt signaling (4,132). Interestingly, it was found that curcumin could inhibit mammosphere formation and could also decrease the amount of aldehyde dehydrogenase-positive cells in normal and malignant breast cancer cells through the inhibition of Wnt signaling (23), suggesting the inhibitory effects of curcumin on breast cancer stem cells (23).…”
Section: Natural Products and Human Healthmentioning
confidence: 93%
“…C. rodentium infection induces epithelial regeneration and repair mechanisms, which drives a marked expansion of undifferentiated colonocytes, resulting in crypt elongation and the presence of undifferentiated colonocytes at the luminal surface (31, 32)(Fig. S1).…”
mentioning
confidence: 99%
“…18 Several lines of evidence suggest that Wnt signaling works in tandem with Notch signaling for intestinal homeostasis and that perturbation of these pathways could lead to inflammation or cancer. 37 The concurrent abrogation of Wnt signaling target genes, such as Lgr5, Ascl2, hTert, and Msi, along with above described changes in Notch targets in the uninvolved region of patients with UC, suggests coordination between Notch and Wnt pathways in UC. These data further emphasize cooperation and hierarchical regulation of more than 1 pathway in the early pathogenesis of the disease wherein Notch primarily affects progenitors while Wnt targets stem cells in the uninvolved region of patients with UC.…”
Section: Discussionmentioning
confidence: 96%
“…37 To determine if Notch signaling is involved in the observed lower crypt defect, we next analyzed the members of Notch signaling and their downstream targets (Fig. 5F).…”
Section: Aberration Of Notch and Wnt Signaling Before Inflammationmentioning
confidence: 99%